2019
DOI: 10.2131/jts.44.347
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of cytochrome P450 genes in the liver of adult zebrafish, <i>Danio rerio</i>

Abstract: Increasing use of zebrafish in biomedical, toxicological and developmental studies requires explicit knowledge of cytochrome P450 (CYP), given the central role of CYP in oxidative biotransformation of xenobiotics and many regulatory molecules. A full complement of CYP genes in zebrafish and their transcript expression during early development have already been examined. Here we established a comprehensive picture of CYP gene expression in the adult zebrafish liver using a RNAseq technique. Transcriptional prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…It should be noticed that in this study we used only male rats. However, several studies reported a significant effect of gender on CYP expression in different animal models, i.e., rodents [57], and, more recently, zebrafish [58]. Further studies are needed to ascertain whether a Western diet effect on drug-metabolizing enzymes is related to gender and to analyze the translational impact of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that in this study we used only male rats. However, several studies reported a significant effect of gender on CYP expression in different animal models, i.e., rodents [57], and, more recently, zebrafish [58]. Further studies are needed to ascertain whether a Western diet effect on drug-metabolizing enzymes is related to gender and to analyze the translational impact of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…It was, therefore, suggested to play a central role in liver physiology and/or xenobiotic biotransformation (Kubota et al 2019). However, in male zebrafish CYP3A65 mRNA accounts for only 6.5% of the total hepatic CYP mRNA content (Kubota et al 2019). This sex-dimorphic expression is contrary to that found in adult killifish (Fundulus heteroclitus), where male fish displayed up to 2.5 -fold higher hepatic CYP3A65 mRNA and protein than female killifish (Hegelund and Celander 2003).…”
Section: Spatiotemporal Expression Patterns Of the Cyp3 Familymentioning
confidence: 99%
“…However, expression of CYP1A does not only vary with age, but also with sex. While CYP1A mRNA accounts for 14.5% of the total hepatic CYP mRNA contents in male zebrafish, it accounts for only 5% in female zebrafish (Kubota et al 2019 ).…”
Section: Spatial and Temporal Cyp Gene Expression Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolic regulators are pre‐eminent in the selection of an animal model for drug toxicity screening procedures (Browning & Horton, 2004). The transcriptional profile of CYP genes shows gender‐specific expression levels, but the major CYP genes present in both the sexes that regulate the xenobiotic metabolism at primary verge are cyp2ad2, cyp3a65, cyp1a, cyp2p9 and cyp2y3 (Alderton et al, 2010; Goldstone et al, 2010; Kubota et al, 2019).…”
Section: Hepatic System Of Zebrafishmentioning
confidence: 99%